Forecasting Farmers’ Terms of Trade in the Plantation Subsector: An ARIMA Approach in Jambi Province - Afisyah, Eva Nur; Zami, Zam; Nurhayani, Nurhayani (Jurnal Prajaiswara, 2026)
Introduction/Main Objectives: Farmers’ Terms of Trade (NTP) is an important indicator used to measure farmers’ welfare, particularly in the plantation subsector which plays a significant role in the regional economy. The fluctuating pattern of NTP in Jambi Province reflects instability in farmers’ welfare due to changes in commodity prices and production costs. This study aims to analyze the trend and forecast the NTP of the plantation subsector in Jambi Province. Background Problems: The main problem addressed in this study is determining an appropriate ARIMA model to accurately forecast the movement of NTP in the plantation subsector in Jambi Province. Research Methods: This research uses a quantitative approach with secondary time series data from 2015–2025 obtained from the Central Statistics Agency. The analytical method applied is ARIMA using the Box-Jenkins approach, including identification, stationarity testing, parameter estimation, diagnostic testing, and model selection based on AIC and SC criteria. Finding/Results: The results show that NTP exhibits a fluctuating but increasing trend, indicating an improvement in farmers’ purchasing power. The selected ARIMA (1,1,1) model is able to capture data patterns and produce reliable forecasts. Conclusion: NTP is projected to increase in the future, indicating potential improvement in farmers’ welfare, with implications for policymakers to maintain price stability and support production efficiency.